Belief, Bounty, and Beauty, Rituals around Sacred Trees in India. - Albertina Nugteren (Numen Book Series, 2005)
This study is focused on the interaction of material and symbolic values in the domain of sacred trees in India. By presenting samples from 3,000 years of Indian ritual practice, it is shown that in many sacred geographies trees continue to connect the present with the past, the material with the symbolic, and the contemporary ecological with the traditionally sacred. Although in India religion may have become very much a temple cult, its embeddedness in the natural world enhances today's 'green' interpretation of religious traditions. That in environmental matters such religious inspiration may be both successful and highly ambivalent at the same time is the thought-provoking position taken in the final chapters.